The AfrAbia+plus Parkinson's disease genomic consortium - Mohamed, Wael Mohamed Yousef; Eltantawi, Mohamed Abdelhalim; Mecheri, Yasser; Zewde, Yared Zenebe; Kamel, Walaa A; Al-Mubarak, Bashayer R; Alzoubi, Karem H (Elsevier, 2024)
Many human studies, including those involving genetics, are conducted in people of northern European ancestry. A lack of ancestral representation in genetics makes it harder to understand the underlying biology of disease, results in unsupported generalisation of current genetics to under-represented groups, limits our capacity to deploy precision therapeutics to only those populations that have been studied, and prevents us from accurately mapping genetic loci. Studies in Parkinson's disease have experienced a similar lack of diversity. The Global Parkinson's Genetics Program (GP2) was initiated in 2020 to meet this need for diversity in research. GP2 seeks to improve understanding of the genetic architecture of Parkinson's disease in a global context. A result of this work was the establishment of the AfrAbia Parkinson's Disease Genomic Consortium (AA-PDGC) in 2023.